Mutable materiality: Illustrations in Jenneth Taylor's children's bibles - Lindquist, Benjamin (Material religion, 2014)
Over the fifty years that Kenneth N. Taylor created children's Bibles, the pictures in these books changed dramatically, yet the text of the Bibles changed little. The relatively standardized text used in these books provides a neutral field where one can better observe the shifting presentation of the scriptural stories. In this essay I investigate how the changing materiality of Taylor's children's Bibles alters the story's meaning for the intended audience. Specifically, I examine the ways in which this material transformation marks a progression away from a hierarchical relationship toward a more democratic connection between parent and child. A number of paratextual adaptations work together to render this reorientation of the parent-child relationship. New illustrations tend to present children as equals to their adult counterparts. Furthermore, a remodeling of these illustrations makes them easier for children to understand, reducing the need for the parent to act as an intermediary. The changing material structure of Taylor's children's Bibles further undermines the hierarchical ritual of parent reading to child, increasing the probability that the child will autonomously engage with the text. Together, these changes position the child as decreasingly preoccupied by the "lower" senses of touch, taste, and smell and more aligned with the constructed Western ideal of a cerebral, non-sensorily oriented being. This adaptability of the Bible's non-textual elements often belies the conservative Christian understanding of a sacred text that conveys a single and immutable reading.